2021
DOI: 10.14202/vetworld.2021.1272-1278
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic effect of Indigofera tinctoria L on Haemonchus contortus obtained from sheep in Indonesia

Abstract: Background and Aim: Hemonchosis has resulted in huge economic losses for sheep farmers worldwide. Secondary metabolite compounds from Indigofera tinctoria L. can be used as anthelmintics. This study aimed to evaluate the in vitro and in vivo effects of I. tinctoria L. aqueous extract (IAE) as an anthelmintic against adult Haemonchus contortus isolated from sheep. Materials and Methods: Ten active adult worms were placed in each Petri dish containing 25 mL of IAE, each having a different concentration of IAE (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…These differences observed between the values of these bioactive constituents and those of other studies depends on factors such as climate, soil physico-chimics constituents, the nature of the solvent used, part of the plant and geographical location of plants [36]. In a study conducted by Ndjonka et al [37] and Muda et al [38] show that the activity of a plant extract depends on the availability of secondary metabolites like tannins; saponins; polyphenols and flavonoids might be responsible for the anthelmintic activity. It is the presence of total phenols, flavonoids and tannins in high concentration which are responsible for anthelmintic activities of the ethanolic extracts of G. arborea.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These differences observed between the values of these bioactive constituents and those of other studies depends on factors such as climate, soil physico-chimics constituents, the nature of the solvent used, part of the plant and geographical location of plants [36]. In a study conducted by Ndjonka et al [37] and Muda et al [38] show that the activity of a plant extract depends on the availability of secondary metabolites like tannins; saponins; polyphenols and flavonoids might be responsible for the anthelmintic activity. It is the presence of total phenols, flavonoids and tannins in high concentration which are responsible for anthelmintic activities of the ethanolic extracts of G. arborea.…”
Section: Discussionmentioning
confidence: 96%
“…It is therefore observed that the plant has a large quantity of secondary metabolites, which can provide a preliminary explanation on its filaricidal activities. Many others studies have shown that plants with anthelmintic activities contain phytochemicals such as polyphenols, tannins, flavonoids, saponins [39]. An others studies done by Fatae et al [40], showed that in nematodes, tannins act on particular proteins called gluthathion s-transferase provoked their inhibitions.…”
Section: Discussionmentioning
confidence: 98%